SISTEMA AQUAPÔNICO INTEGRA PRODUÇÃO DE LAMBARI-DO-RABO-AMARELO COM ALMEIRÃO - AMARO, Luelyton Silva; WANDERLEY, Alysson Martins; MENDEZ, Victor Hugo Benassi; ACUNHA, Rubia Mara Gomes; CALVES, Gleice de Souza; CAMPOS, Cristiane Meldau (ANAIS DO ENIC, 2026)
.